PENGARUH SEKTOR PARIWISATA TERHADAP PERTUMBUHAN EKONOMI DI KOTA PALOPO - Hasriadi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The tourism sector is one of the most potential resources for economic development in a region or even a country. The tourism sector is a potential leading sector in Palopo City, as evidenced by the various tourist attractions in Palopo City. This study seeks to see how the influence of the tourism sector on economic growth in Palopo City. This research was conducted in Palopo City. The type of data used is a time series from 2011 to 2021, which comes from the Palopo City Tourism Office, the Central Bureau of Statistics and books. Data analysis technique uses Simple Regression with Statistical Packages For Social Science (SPSS). The results of this study indicate that the tourism sector has no effect and is not significant on economic growth in Palopo City by concluding that economic growth can be seen from several aspects not only in the tourism sector.